Static structure analysis of EMU CR400AF high speed train’s hollow axle using ansys workbench - Tito Syahril Sobarudin Izha Mahendra; Muhamad Fitri (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
One of the important components in a train is the wheel axle part whose main function is to distribute the load on the train body to the wheels towards the rails. On conventional trains, train wheel axles still often have material failures in the form of cracks and even breaks. The wheel shaft used by conventional trains is solid while the one used in the fast train uses a hollow axle so that the risk is greater. To confirm and confirm the strength of the hollow axle structure, it is necessary to analyze the structure of the hollow axle when receiving static loading due to the load of the train body. The parameters measured are maximum stress, safety of factor, and maximum deformation. The analysis process is carried out using manual theoretical calculations and simulations with finite element methods using ANSYS Workbench software. In the theoretical calculation, the maximum stress value is 59.71 MPa and the safety factor value is 8.87, and the simulation results get a maximum stress of 62.02 MPa, a safety factor value of 8.54, and the maximum deformation that occurs is only 0.086mm. The difference from the theoretical calculation and simulation of the maximum stress and safety of the factor was 3.70% and 3.72%. Based on the results obtained, it can be concluded that the hollow axle is safe because the maximum stress < the material allowable voltage and the safety of factor (SF) value < the material standard value of 4,5